(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
In 2012, a directive of the European Commission required recognition of non-formal and informal learning. As it states: "Every Citizen has the right to have their learning recognized and validated, irrespective of the context in which the learning occurred." This directive recognized citizens as life-wide and life-long learners, irrespective of the socio-economic background of their parents and grandparents. The promise of recognition outside the youth-focused, concentrated, formal education was inspiring and ground-breaking! The European Qualifications Framework (EQF) articulates level-specific outcomes for qualifications. When re-contextualized to non-formal settings, this recognizes “lived experience.” CLOCK Your Skills, established in 2016, is neither higher nor further Education, rather, it makes invisible skills visible and valued. CLOCK is a structured process that helps people turn their real-world experience—like work, community involvement, or self-directed learning—into recognized credentials. Participants document what they’ve done in a portfolio of evidence, which is then reviewed by experienced practitioners (“Sector Experts”) from their field. These experts assess the work through peer-based evaluation and guided reflection, focusing on what the person can actually do, not how they performed in school. The result is a formal or digital credential aligned to qualification frameworks, making informal learning visible, comparable, and usable for career or educational advancement. This presentation showed how CLOCK’s international community has fueled equity, diversity, and inclusion through recognition and empowerment, smashed glass ceilings, defeated imposter syndrome, carried out professional peer reviews, and issued digital badges and certificates. As the presentation pointed out, CLOCK is for non-formal learners at all levels. Keywords: community of learning, recognition of non-formal learning; digital credentials, European Qualifications Framework, digital badges, clock your skills